Teachers and conflict situations at a Night Secondary School (Praxis Educativa, 2012)
This article presents some preliminary results about the investigation “Institutional times as an analysis instrument in the teacher practices at a Night Secondary School” which is being developed at the Comahue National University (2005- 2007). This paper shows a synthesis of the different pedagogical positions about conflicts in education institutions. It analyses some teachers’ discourses in connection with what they consider as conflict situations in the institutional spaces of a night center of education. The Teacher Training is questioned –related to a pedagogical and even social model– to consider if it allows the teachers to see some questions inside schools, to face what it is happening there and to act and analyse the assumptions that back up the specific teaching practices. That’s why it is necessary to analyse the representations that teachers have about conflicts, how they place themselves in front of these situations and which is the impact their training has when they have to solve or deal with conflicts.
Keywords: teacher practice; conflicts; teacher discourse; night school; Teacher Training